Kecemasan sosial pada remaja pengguna media sosial: Menguji peranan body image - Prastia, Tissa; Herlan Pratikto; Suhadianto (INNER: Journal of Psychological Research, 2023)
Abstract The background of this research is that adolescents in the Kapasari Village, Surabaya City, experience social anxiety due to benchmarks or self-evaluations about their appearance and self-satisfaction when they see other people's posts on social media. This study aims to determine the relationship between body image and social anxiety. This study uses quantitative methods to achieve research objectives. The subjects used in this study were teenagers in the Kapasari sub-district, Surabaya City. The population is 1200 and 291 samples, the sample size of this study is formulated using krejcie tables. The research data were analyzed using the Spearman Rho correlation test with the help of the IBS SPSS version 26.0 for window computer program. The calculation results of the data analysis show that the Spearmans Rho correlation coefficient is 0.830 with a significance of 0.01 (p <0.01), which means that there is a very significant relationship between body image and social anxiety in adolescent social media users in Surabaya. Keywords : social anxiety, body image, youth, social media.